Effective digital marketing implementation to reimburse effect of Covid-19 on tourism industry and Opatrip.com - Islam Adib, Md. Rafiul (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.